Clinical management initiatives undertaken by nurses in a strategic leadership position (Research, Society and Development, 2021)
In the present study, it is proposed to characterize clinical management initiatives undertaken by nurses in a strategic leadership position. For this, a descriptive, exploratory, qualitative research was developed between September and October 2018, with the participation of eight nurses in leadership positions in primary health care in a municipality in the south of Brazil. The same findings to be identified audio-recorded, questioning focused on the management-assistance-education axes in the participants' practices. Afterwards, content analysis was carried out, thematic modality. The results illustrate proactive dispositions to achieve the best results with regard to the management of care practices, the orientation of actions focused on the needs of users and the professional development of the team on a permanent basis. The clinic management initiatives undertaken by nurses in leadership positions reveal ample opportunities for the dissemination of innovative and effective practices in health services, and announce the strategic potential of these professionals in conducting management processes that incite movements in favor of the organization in networks with with a view to producing safe, quality care based on standards of excellence.